Evaluation of Laterally Graded Silicon Germanium Wires for Thermoelectric Devices Fabricated by Rapid Melting Growth. (20th July 2018) - Yokogawa, Ryo; Hashimoto, Shuichiro; Takahashi, Kouta; Oba, Shunsuke; Tomita, Motohiro; Kurosawa, Masashi; Watanabe, Takanobu; Ogura, Atsushi
Abstract : To achieve high thermoelectric performance, laterally graded silicon germanium (SiGe) wires were fabricated by rapid melting growth (RMG) method. In addition, the structure evaluation of the RMG laterally graded SiGe wire were performed by Raman spectroscopy and electron backscattering pattern (EBSP). Ge fraction x and strain were estimated from one-dimensional distribution of Raman shift for Ge-Ge mode. As a result, an apparent change of Ge fraction x was observed. For, biaxial isotropic strain assumption, good agreement among the obtained Ge fraction x distribution and theoretical values in the RMG laterally graded SiGe wire near Si seed area were shown. Crystal orientation mapping was obtained by EBSP. It was revealed that the crystal orientation in the SiGe wire was changed from [001] to [110] with increasing growth length. These changes may also influence electronic and thermoelectric performance dramatically.